Tainted Ground: Screenplay Development With Genre Swinging in Mind - Gadiuta, Filip (Auckland University of Technology, 2015)
The research in my exegesis is framed around screenplay structure, horror genre trends, and genre-mixing. I wanted to create a screenplay grounded in the horror genre which benefited structurally from mixing with a supporting genre. I experienced difficulties in realizing key relationships while my screenplay was still intended as a horror crime series pilot. I feel the screenplay’s development toward a horror mystery feature film helped meet my expectations in the end. The genre discussion is integral to the approach. Especially since there are multiple genres that combine in the present screenplay. This genre mixing is discussed to support the concept of ‘genre-swinging.’ This is a term I coined after reflecting on the incidences observable in films where the preponderant genre is strengthened by ancillary. The specific occurrences I identify is that the film’s focus shifts between the genres for dramatic effect. In these conditions, the main genre is at times overseen by the intricacies brought about by the supporting genres that may attract wider audiences and compound the structural impact on the drama. In my exegesis, I posit the research question of ‘How does genre-swinging influence the development of a feature-length horror screenplay?’ I follow this question by looking at theoretical aspects of feature films and television series that respond to my inquiry. I discus the theoretical aspects in relation to the practical achievements discernable in the development process. Thus, I am able to explore in depth the ways in which genres do mix and the effects achieved. I attempt to interpret the benefits that mixing the horror genre in particular derives from this genre-swinging. I continue to discuss my screenplay against the characteristics that I envisaged for genre-swinging, comparing and contrasting with the materials I researched. Going through the stages of actually producing a work that may demonstrate the characteristics of genre-swinging, I became more alert to the technique that characterizes iconic films of the horror genre. I conclude that horror is a malleable genre which acquires the desired effect in a compensatory quality. As horror cannot have the desired impact on audiences neglecting its key features, (fear, themes of death, the unknown, the mysterious and the unexplained.) it can be compensated by other genres. Audiences that do not appreciate the horror elements presented in a story may still accept the impact of the supporting genre(s). Here, genre-swinging allows horror to gather emotional significance for plot points and mood/tone it may otherwise lack. Alternatively, the emotional significance developed by the supporting genre may be compounded if the horror elements elicit audience response. Lastly, emotional significance of either genre may be supplemented by specific elements which may not be achieved without genre-swinging.
Keywords: Screenplay; Horror; Genre; Genre swinging; Genre-swinging; Story structure